Conceptualizing the Circular Economy (Revisited): An Analysis of 221 Definitions - Kirchherr, Julian; Yang, Nan-Hua Nadja; Schulze-Spüntrup, Frederik; Heerink, Maarten J.; Hartley, Kris (Resources, conservation and recycling, 2023)
•Most comprehensive analysis of circular economy definitions in scholarly discourse.•221 definitions examined, many mentioning that a fundamental shift is needed for CE.•Questions linger regarding compatibility of sustainability and economic growth.•Varied understandings about CE can result in concept collapsing or being deadlocked. In the past decade, use of the circular economy (CE) concept by scholars and practitioners has grown steadily. In a 2017 article, Kirchherr et al. found that the CE concept is interpreted and implemented in a variety of ways. While multiple interpretations of CE can enrich scholarly perspectives, differentiation and fragmentation can also impede consolidation of the concept. Some scholarship has discussed these trends in context-specific cases, but no large-scale, systematic study has analysed whether such consolidation has taken place across the field. This article fills this gap by analysing 221 recent CE definitions, making several notable findings. First, the concept has seen both consolidation and differentiation in the past five years. Second, definitional trends are emerging that potentially have more meaning for scholarship than for practice. Third, scholars increasingly recommend a fundamental systemic shift to enable CE, particularly within supply chains. Fourth, sustainable development is frequently considered the principal aim of CE, but questions linger about whether CE can mutually support environmental sustainability and economic development. Finally, recent studies argue that CE transition relies on a broad alliance of stakeholders, including producers, consumers, policymakers, and scholars. This study contributes an updated systematic analysis of CE definitions and conceptualizations that serves as an empirical snapshot of current scholarly thinking. It thereby provides a basis for further research on whether conceptual consolidation is needed and how it can be facilitated for practical purposes. [Display omitted]